2018
DOI: 10.3389/fphys.2018.01539
|View full text |Cite|
|
Sign up to set email alerts
|

Pacing Strategies in the ‘Athens Classic Marathon’: Physiological and Psychological Aspects

Abstract: Despite the increased scientific interest in the relationship between pacing and performance in marathon running, little information is available about the association of pacing with physiological and psychological parameters. Therefore, the aim of the present study was to examine the role physical fitness and training characteristics on pacing in the ‘Athens Classic Marathon.’ Finishers in this race in 2017 (women, n = 26, age 40.8 ± 9.4 years; men, n = 130, age 44.1 ± 8.6 years) were analyzed for their pacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…This is an interesting finding, as other studies have shown the fastest ultramarathon competitors to be 35 years old on average, regardless of their sex [ 28 , 29 ]. Our observation that the fastest men were younger than the fastest women could be attributed to age-related declining testosterone [ 30 , 31 ] and the associated decrease in maximum oxygen capacity and relative muscle mass [ 32 , 33 , 34 ]. Especially in runs with a lot of altitude difference like the UTMB ® , the cumulative strain on the osteoarticular and musculotendinous systems is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an interesting finding, as other studies have shown the fastest ultramarathon competitors to be 35 years old on average, regardless of their sex [ 28 , 29 ]. Our observation that the fastest men were younger than the fastest women could be attributed to age-related declining testosterone [ 30 , 31 ] and the associated decrease in maximum oxygen capacity and relative muscle mass [ 32 , 33 , 34 ]. Especially in runs with a lot of altitude difference like the UTMB ® , the cumulative strain on the osteoarticular and musculotendinous systems is high.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because more men participated in the race (12,681 men and 1148 women). Another possible reason could be that in terrain with more variation of altitude, men are potentially able to run uphill faster due to their higher relative muscle mass compared to fat mass [ 34 , 42 , 43 ]. The small number of women participating in the race, making up merely 11% of all finisher results, is striking.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in HR during prolonged endurance competitions is a feature influenced by several factors such as substrate depletion (e.g., glycogen), altered substrate utilization, fluid and electrolyte imbalances, altered muscle efficiency, thermoregulatory problems, cardiac and neuromuscular fatigue, and psychological factors (O'Toole and Douglas, 1995;Neumayr et al, 2004). Furthermore, it was demonstrated that the lower the aerobic capacity, the greater the decline in performance across a race (Nikolaidis and Knechtle, 2018b). A high aerobic work capacity can assist athletes to maintain their race speed by preventing fatigue (Sjodin and Svedenhag, 1985;Coyle, 1995) based on higher VO 2max , anaerobic threshold performance, and running economy.…”
Section: Groupmentioning
confidence: 99%
“…Studies on marathon runners have used several assessment methods of BF and other measures of body composition, such as muscle mass. BF has been widely assessed using skinfolds' thickness in seven [6,7] and ten sites [8]. Not only the quantity, but also the distribution of fat has health implications, with central fat related to risk for diseases such as coronary heart disease and stroke, whereas peripheral fat has less metabolic risk [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the abovementioned studies have enhanced our understanding of anthropometric characteristics and the body composition of marathon runners, little information exists so far about the variation of skinfold thickness by anatomical site. Since the number and location of anatomical sites used for skinfold thickness assessment in this sport varied by study [6][7][8], knowledge on the variation of skinfold thickness by anatomical site would be of great practical importance for practitioners to effectively monitor the body composition of their athletes. For instance, it is well-known that fast and slow marathon runners differed in BF estimated by the sum of skinfolds [1,12]; however, the anatomical sites that accounted for this variation have not been examined so far.…”
Section: Introductionmentioning
confidence: 99%